RETRACTED: The modern paradigm for the development of the regional transport complex - Sukhinin Sergey; Novoselova Irina; Petrov Konstantin; Firsov Vladimir; Popov Egor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001